Suburbia and Rural Landscapes in Medieval Sicily - Barba, Angelo Castrorao; Mandalà, Giuseppe (2023)
Suburbia and Rural Landscapes in Medieval Sicily presents the results of the main ongoing archaeological and historical research focusing on medieval suburbia and rural sites in Sicily. It is thus intended to update traditional views regarding the evolution of this territory from Late Antiquity to the Middle Ages by bringing into the picture new data from archaeological excavations undertaken at several sites across Sicily, new information from surveys of written sources, and new reflections based on the analysis of both material and documentary sources. The volume is divided into thematic areas: Urbanscapes, suburbia, hinterlands; Inland and mountainous landscapes; Changes in rural settlement patterns; and Defence and control of the territory. The essays underline the fundamental contribution of archaeological research in Sicily to the debate on the formation of early medieval landscapes at the crossroads between the Byzantine and Islamic worlds. A comparison with other research areas and constant dialogue with historical sources constitute essential elements for advancing our knowledge of the rural and suburban world of Sicily as a case study illustrating wider Mediterranean dynamics.